2016
DOI: 10.1038/srep37058
|View full text |Cite
|
Sign up to set email alerts
|

Single GDP-dissociation Inhibitor Protein regulates endocytic and secretory pathways in Leishmania

Abstract: The role of GDP dissociation inhibitor (GDI) protein in regulation of Rab cycle in Leishmania is not known. Here, we have cloned and characterized the functions of GDI homologue in vivo in Leishmania. Our results have shown that LdGDI:WT along with GDP removes the Rab5 from purified endosomes and inhibits the homotypic fusion between early endosomes. Whereas, LdGDI:R239A, a dominant negative mutant of GDI, under the same condition neither removes the Rab5 from endosome nor inhibits fusion. To determine the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…The vesicular cargo movement is coordinated by Rab proteins, which act as global molecular switches. In Leishmania, Rab functions are vital for the leishmaniasis infection and propagation [12]. Endocytic functions of Rab5 and Rab7 [10,12] and secretory role of Rab1 [8] have been experimentally reported.…”
Section: Discussionmentioning
confidence: 99%
“…In Leishmania, Rab functions are vital for the leishmaniasis infection and propagation [12]. Endocytic functions of Rab5 and Rab7 [10,12] and secretory role of Rab1 [8] have been experimentally reported. Biophysical characteristics of a recombinant Rab5 have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation